Breaking into the Foam: Peter Sloterdijk's Philosophy of Dwelling and Richard Stark's Parker Novels. (March 2021) - Phipps, Gregory
Abstract : This article brings together the crime fiction novels of Richard Stark (a pseudonym of Donald Westlake) and the philosophical ideas of Peter Sloterdijk. Influential and yet critically neglected, Stark's 'Parker novels' feature an amoral and unchanging thief named Parker who infiltrates and exploits an array of settings for his criminal activities. Two of the main recurring situations in these novels involve Parker either breaking into and searching the home of a rival or using an empty home as a temporary hideaway. This article argues that Parker's approach to homes invokes elements in Sloterdijk's theorization of dwellings, including his broad theory that contemporary Western society is arranged in a manner reminiscent of bubbles in a 'mountain of foam', as well as his specific ideas about how contemporary dwellings function as spheres that aim for both individualistic privacy and access to mobile networks. The article draws upon these theories to explore how Stark's novel Flashfire represents Parker's attempts to establish a private sphere for his own use in Palm Beach, Florida, a process which ultimately exposes the limits of the 'foam' that composes his world of heists and brutal practicality.